Chronic reduction of synaptic proteins in the epileptogenic lesion of patients with hippocampal sclerosis - Akiko Oota-Ishigaki; Nami Suzuki; Keiya Iijima; Yutaro Takayama; Yuiko Kimura; Kotaro Hattori; Masaki Iwasaki; Takashi Hayashi; Takashi Hayashi (Frontiers in Molecular Neuroscience)
Disturbance of synaptic proteins in the epileptogenic lesion is considered the basis for drug-resistant focal epilepsy. However, details of these molecular changes remain unknown because brain tissues are typically uncollectable from live patients. Using surgically excised brain tissues from epileptogenic lesions of patients with hippocampal sclerosis, we biochemically studied quantitative alterations in synaptic protein expression and their posttranslational phosphorylation of synaptic proteins, including glutamate receptors, which are the major excitatory neurotransmitter receptors. Compared to less epileptogenic control regions, most patients exhibited reduced synaptic protein expression in the lesion and decreased α-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA) receptor phosphorylation in the epileptogenic lesion, indicating an overall weakening of synapses in the chronic condition. These molecular disturbances may explain the clinically observed basal hypoactivity and hypometabolism in epileptogenic lesions and may function as a fundamental mechanism of epileptogenesis. Furthermore, a history of febrile seizures is associated with increased AMPA receptor phosphorylation, which correlates with the enhancement of excitatory synaptic strength and reduced thresholds of hyperexcitation.